Anatomical, pathological, and histological features of experimental respiratory infection of birds by biofilm-forming bacteria Staphylococcus aureus - Ekaterina Lenchenko; Nadezhda Sachivkina; Olesya Petrukhina; Nikolay Petukhov; Andrey Zharov; Natallia Zhabo; Marina Avdonina (Veterinary World, 2024)
Background and Aim: The pathogenesis of staphylococcal infections is mediated by virulence factors, such as enzymes, toxins, and biofilms, which increase the resistance of microorganisms to host immune system evasion. Testing and searching for standardized multi-level algorithms for the indication and differentiation of biofilms at the early stages of diagnosis will contribute to the development of preventive measures to control the critical points of technology and manage dangerous risk factors for the spread of infectious diseases. This research aimed to study the main stages of Staphylococcus aureus biofilm formation in in vitro experiments and to analyze the dynamics of respiratory syndrome development in chickens infected with these bacteria.